(untitled) (TAMADDUN NURI JURNALI, 2025)
This article examines effective strategies for teaching speech skills in the context of Uzbek-Russian bilingualism. Approaches to developing communicative skills in bilingual students are analyzed. The main focus is on integrating Uzbek and Russian languages ​​into the educational process. The author asserts that a comprehensive approach to education makes it possible to effectively develop speech skills and improve bilingual interaction.